Electrochemical devices and electronic devices

By using the compound of formula I and lithium salt additives in the electrochemical device to form a stable SEI film and protective film, the shortcomings of the electrochemical device in high-temperature storage and cycling performance are solved, and the overall performance of the battery is significantly improved.

CN114744294BActive Publication Date: 2025-01-10NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210314427.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-28
Publication Date
2025-01-10
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

The existing electrochemical devices have shortcomings in high-temperature storage and cycling performance, especially the side reaction between the negative electrode and the electrolyte leads to increased gas production and slow lithium ion transmission speed, affecting the overall performance of the battery.

Method used

Using an electrolyte containing a compound of formula I, a stable SEI film is formed on the surface of the negative electrode to reduce side reactions, and a protective film is formed on the surface of the positive and negative electrode through lithium salt additives and sulfur-containing double bond compounds, thereby improving the oxidation stability of the electrolyte. and interface stability.

Benefits of technology

It significantly improves the circulation performance and high-temperature storage performance of electrochemical devices, reduces the consumption and gas production of electrolytes, and improves the transmission speed and interface stability of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114744294B_ABST
    Figure CN114744294B_ABST
Patent Text Reader

Abstract

The present application provides an electrochemical device, comprising a negative electrode sheet and an electrolyte, wherein the electrolyte comprises a compound represented by formula I, and the negative electrode sheet comprises a negative electrode active material, wherein the specific surface area of ​​the negative electrode active material is am 2 / g, the value range of a is 0.1-5; wherein, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%; a and b satisfy the relationship: 0.1≤a / b≤500. The present application can significantly improve the cycle performance and high temperature storage performance of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art

[0002] As a new type of portable energy storage device, electrochemical devices (such as lithium-ion secondary batteries) have been widely used in portable electronic devices such as mobile phones, laptops, and cameras due to their high energy density, high operating voltage, long cycle life, no memory effect, and green environmental protection. Their scope of use is also expanding from small portable electronic devices to large electric transportation vehicles and renewable energy storage.

[0003] As a key component of electrochemical devices, electrolytes transport lithium ions between the positive and negative electrodes, affecting the cycle life, capacity performance, and safety performance of electrochemical devices. With the expansion of the application of electrochemical devices, the performance of electrochemical devices, such as high-temperature storage performance and cycle performance, is increasingly required, which also places higher requirements on electrolytes. Summary of the invention

[0004] In view of the problems existing in the background technology, the purpose of the present application is to provide an electrochemical device with excellent high-temperature storage performance and cycle performance.

[0005] In order to achieve the above object, the present application provides an electrochemical device, including a negative electrode sheet and an electrolyte, wherein the electrolyte contains a compound represented by formula I,

[0006]

[0007] Wherein, R1 is selected from any one of substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C1 to C6 alkoxy, substituted or unsubstituted C2 to C6 alkenyl, wherein when substituted, the substituent is selected from cyano and halogen atoms;

[0008] R2, R3, R4, R5 and R6 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C2 to C 10 Alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C2 to C 10 Any one of the heterocyclic groups, wherein, when substituted, the substituent is a halogen atom;

[0009] Any two groups among R2, R3, R4, R5 and R6 may be bonded to form a ring structure;

[0010] The substituted or unsubstituted C2 to C10 The heterocyclic group includes substituted or unsubstituted C6 to C 10 Aromatic heterocyclic group, substituted or unsubstituted C2 to C 10 Alicyclic group, wherein the heteroatom is selected from N or O;

[0011] The negative electrode sheet includes a negative electrode active material, and the specific surface area of ​​the negative electrode active material is am 2 / g, and the value range of a is 0.1-5.

[0012] Wherein, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%;

[0013] The a and b satisfy the relationship: 0.1≤a / b≤500.

[0014] In some embodiments, the specific surface area of ​​the negative electrode active material is am 2 / g, and the value range of a is 0.5-3.5.

[0015] In some embodiments, a and b satisfy the relationship: 0.8≤a / b≤300.

[0016] In some embodiments, the compound of formula I comprises any one of the following structural formulas:

[0017]

[0018]

[0019] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%, and the value range of b is 0.005-3.

[0020] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%, and the value range of b is 0.005-1.

[0021] In some embodiments, the electrolyte further includes ethylene carbonate and propylene carbonate.

[0022] Based on the mass of the electrolyte, the content of ethylene carbonate is c%, the content of propylene carbonate is d%, and c and d satisfy the relationship: 10≤c+d≤40.

[0023] In some embodiments, based on the mass of the electrolyte, the content of ethylene carbonate is c%, the content of propylene carbonate is d%, and c and d satisfy the relationship: 20≤c+d≤40. In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector.

[0024] The compaction density of the negative electrode sheet is eg / cm3, and the value range of e is 1-2.

[0025] In some embodiments, the compaction density of the negative electrode sheet is eg / cm 3 , the value range of e is 1-1.5.

[0026] In some embodiments, the electrolyte further comprises a compound containing a sulfur-oxygen double bond.

[0027] Based on the mass of the electrolyte, the mass percentage of the compound containing sulfur-oxygen double bonds is f%, and the value range of f is 0.01-5.

[0028] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound containing sulfur-oxygen double bonds is f%, and the value range of f is 0.05-4.

[0029] In some embodiments, the compound containing sulfur-oxygen double bonds includes at least one of methanedisulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propanedisulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate.

[0030] In some embodiments, the electrolyte further includes a lithium salt additive; the lithium salt additive includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium difluorophosphate or lithium trifluoromethanesulfonate; based on the mass of the electrolyte, the mass percentage content of the lithium salt additive is g%, and the value range of g is 0.01-5.

[0031] In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt additive is g%, and the value range of g is 0.01-3.5.

[0032] In some embodiments, the present application also provides an electronic device, which includes the above-mentioned electrochemical device.

[0033] This application has at least the following beneficial effects:

[0034] The present application can significantly improve the cycle performance and high-temperature storage performance of electrochemical devices. DETAILED DESCRIPTION

[0035] The exemplary embodiments are described in detail below, but these exemplary embodiments can be implemented in different ways and should not be interpreted as being limited to the embodiments described in this application. On the contrary, the purpose of providing these embodiments is to make the disclosure of this application thorough and complete, and to fully convey the scope of this application to those skilled in the art.

[0036] In the description of the present application, unless otherwise clearly specified and limited, the terms "Formula I", "first additive" and the like are used for illustrative purposes only and are not to be understood as indicating or implying relative importance and mutual relationship.

[0037] [Electrochemical device]

[0038] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium-ion battery.

[0039] In some embodiments, the electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, and a housing.

[0040] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0041] <Electrolyte>

[0042] In some embodiments, the electrolyte comprises a compound of formula I,

[0043]

[0044] Wherein, R1 is selected from any one of substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C1 to C6 alkoxy, substituted or unsubstituted C2 to C6 alkenyl, wherein when substituted, the substituent is selected from cyano and halogen atoms;

[0045] R2, R3, R4, R5 and R6 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C1 to C 10Alkyl, substituted or unsubstituted C2 to C 10 Alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C2 to C 10 Any one of the heterocyclic groups, wherein, when substituted, the substituent is a halogen atom;

[0046] Any two groups among R2, R3, R4, R5 and R6 may be bonded to form a ring structure;

[0047] The substituted or unsubstituted C2 to C 10 The heterocyclic group includes substituted or unsubstituted C6 to C 10 Aromatic heterocyclic group, substituted or unsubstituted C2 to C 10 Alicyclic group, wherein the heteroatom is selected from N or O;

[0048] The negative electrode sheet includes a negative electrode active material, and the specific surface area of ​​the negative electrode active material is am 2 / g, the value range of a is 0.1-5;

[0049] Wherein, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%;

[0050] The a and b satisfy the relationship: 0.1≤a / b≤500.

[0051] In some embodiments, the value of a ranges from 0.5 to 3.5.

[0052] In some embodiments, a and b satisfy the relationship: 0.8≤a / b≤300.

[0053] Adding the compound of formula I to the electrolyte can significantly improve the cycle and high-temperature storage performance of the electrochemical device. This is mainly because the compound of formula I can form a stable SEI film on the surface of the negative electrode, improve the interface stability of the negative electrode, reduce the side reaction between the negative electrode and the electrolyte, reduce the consumption of solvents and additives in the electrolyte during the cycle and storage process, and reduce gas production; in addition, the nitrogen-containing cation part in the compound of formula I can not only promote the dissociation of active metal ion salts such as lithium salts, but also complex with Lewis bases such as ethylene carbonate (EC) in the electrolyte, thereby improving the oxidation stability of the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0054] When the specific surface area of ​​the negative electrode active material is large, the side reactions between the active material and the electrolyte will increase, causing an increase in gas production. At this time, a larger content of the compound of formula I is required to protect the negative electrode active material and improve the gas production problem; when the specific surface area of ​​the negative electrode material is large, the contact between the active material particles is poor, resulting in a slower transmission rate of active metal ions such as lithium ions, thereby reducing the cycle performance of the electrochemical device; although the SEI film formed by the compound of formula I can protect the negative electrode interface, the impedance of the SEI film is large, so an appropriate amount of the compound of formula I should be added under the premise of ensuring the improvement of the performance of the electrochemical device, so the specific surface area of ​​the negative electrode active material in this application is am 2 / g and the mass percentage b% of the compound of formula I satisfy the relationship 0.5≤a / b≤300. When the two satisfy the above relationship, the cycle performance and high-temperature storage performance of the electrochemical device can be synergistically improved.

[0055] In some embodiments, the compound of formula I comprises any one of the following structural formulas:

[0056]

[0057]

[0058] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%, and the value range of b is 0.005-3. The compound of formula I can form a stable SEI film on the surface of the negative electrode, improve the stability of the negative electrode interface, reduce the side reaction between the negative electrode and the electrolyte, and reduce gas production. The nitrogen-containing cations in the compound of formula I can promote the dissociation of active metal ion salts, and can also complex with ethylene carbonate (EC) in the electrolyte to improve the oxidative stability of the electrolyte, thereby improving the cycle performance and high temperature storage performance of the electrochemical device. When the content of the compound of formula I is low, the improvement effect is not obvious. When the content of the compound of formula I is high, the impedance of the SEI film formed increases, affecting the performance of the electrochemical device. In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%, and the value range of b is 0.005-1. At this time, the electrochemical device has better cycle performance and high temperature cycle performance.

[0059] In some embodiments, the electrolyte further includes ethylene carbonate and propylene carbonate; based on the mass of the electrolyte, the mass percentage of ethylene carbonate is c%, the mass percentage of propylene carbonate is d%, and c and d satisfy the relationship: 10≤c+d≤40.

[0060] Increasing the ethylene carbonate (EC) content in the electrolyte can improve the cycle performance of the electrochemical device. This is because ethylene carbonate has a high dielectric constant and can improve the conductivity of the electrolyte. However, when the EC content is too high, more side reactions will occur between the electrodes, causing increased gas production during high-temperature storage. When combined with a certain amount of propylene carbonate (PC), PC can improve the conductivity and high-temperature performance of the electrolyte and reduce gas production. However, when the PC content is too high, it may cause damage to the negative electrode structure and affect the cycle performance of the electrochemical device. When the sum of the contents of ethylene carbonate and propylene carbonate is within the above range, the cycle performance and high-temperature storage performance of the electrochemical device can be further improved.

[0061] In some embodiments, the electrolyte further includes a compound containing a sulfur-oxygen double bond; based on the mass of the electrolyte, the mass percentage of the compound containing a sulfur-oxygen double bond is f%, and the value range of f is 0.01-5.

[0062] Adding sulfur-oxygen double bond compounds to the electrolyte can significantly improve the high-temperature storage performance of the electrochemical device. This is mainly because sulfur-oxygen double bond compounds can form a protective film on the surface of the positive and negative electrodes. The protective film has a compact structure and low impedance, which can not only effectively inhibit the dissolution of transition metals but also provide good protection for the electrode interface, reduce the side reactions between the electrolyte and the positive and negative electrodes, and reduce the gas production inside the electrochemical device. When the amount of sulfur-oxygen double bond compounds is too high, it will not further reduce the gas production, but may increase the transmission impedance of active ions in the electrolyte and reduce the cycle performance of the electrochemical device.

[0063] In some embodiments, the compound containing sulfur-oxygen double bonds includes at least one of methanedisulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propanedisulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate.

[0064] In some embodiments, the electrolyte further comprises a lithium salt additive; the lithium salt additive comprises at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium difluorophosphate or lithium trifluoromethanesulfonate. In some embodiments, based on the mass of the electrolyte, the mass percentage content of the lithium salt additive is g%, and the value range of g is 0.01-5.

[0065] Lithium salt additives can form a stable protective film at the interface of the positive and negative electrodes, reduce side reactions between the electrolyte and the positive and negative electrodes, reduce gas production, and improve the cycle performance and high-temperature storage performance of the electrochemical device. When the content of lithium salt additives is low, a uniform protective film cannot be formed at the interface of the positive and negative electrodes, and effective protection cannot be achieved; when the content of lithium salt additives is high, a thicker protective film is formed at the negative electrode interface, resulting in a larger negative electrode interface impedance, which may cause active metal ions to precipitate at the negative electrode interface during the cycle of the electrochemical device.

[0066] The combined use of the above additives can simultaneously increase the stability of the positive and negative electrodes of lithium-ion batteries, and effectively improve the high-temperature storage and cycle performance of electrochemical devices.

[0067] <Negative electrode>

[0068] In some embodiments, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, and the specific surface area of ​​the negative electrode active material is am 2 / g, and the value range of a is 0.1-5. When the specific surface area of ​​the negative electrode active material is too large, it is easy to cause a side reaction between the negative electrode active material and the electrolyte, resulting in increased gas production. At the same time, when the specific surface area of ​​the negative electrode active material is large, it will cause the water content inside the material to increase, and the negative electrode active material will undergo a side reaction to generate HF, corroding the negative electrode structure. When the specific surface area of ​​the negative electrode active material is too small, the transmission speed of the active ions is slow, affecting the cycle performance of the electrochemical device.

[0069] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector; the negative electrode sheet has an average surface area of ​​eg / cm 3 , the value range of e is 1-2. When the compaction density of the negative electrode sheet is high, it is easy to cause the active material particles to break and cause electrical connection failure. When the compaction density of the negative electrode sheet is low, the connection between the active particles is poor, which affects the insertion / extraction of active ions and the cycle performance of the electrochemical device. When the compaction density of the negative electrode sheet is within the above range, the electrical connection between the active particles and the electrolyte can be guaranteed to have a good infiltration effect, further improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0070] The negative electrode includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and an X-ray photoelectron energy spectrum of the negative electrode active material layer has a peak at 395 eV to 406 eV.

[0071] In some embodiments, the negative electrode active material layer further comprises a negative electrode binder and a negative electrode conductor. In some embodiments, the negative electrode binder comprises at least one of difluoroethylene-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon.

[0072] In some embodiments, the specific type of the negative electrode conductive agent is not limited and can be selected according to needs. As an example, the conductive agent includes but is not limited to at least one of conductive graphite, superconducting carbon, Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0073] In some embodiments, the negative electrode active material layer further includes a thickener. The specific type of the thickener is not limited and can be selected according to needs. As an example, the thickener includes but is not limited to sodium carboxymethyl cellulose (CMC).

[0074] In some embodiments, the negative electrode sheet also includes a current collector. The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to copper foil, copper alloy foil, aluminum foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector, etc. In the present application, there is no particular restriction on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. In the present application, the negative electrode active material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. The present application has no particular restrictions, as long as the purpose of the present application can be achieved.

[0075] In some embodiments, the method for preparing the negative electrode sheet is a method for preparing the negative electrode sheet that can be used for an electrochemical device that is well known in the art. In some embodiments, the negative electrode active material and the optional conductive agent, binder and thickener are usually dispersed in a solvent to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained through processes such as drying and cold pressing. The solvent is a solvent that can be used as a negative electrode active material layer that is well known in the art, and the solvent is, for example, but not limited to, water. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but the present application is not limited thereto.

[0076] <Positive electrode>

[0077] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The positive electrode material layer generally includes a positive electrode active material and an optional positive electrode binder and a conductive agent. In the present application, there is no particular restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to aluminum foil, aluminum alloy foil or a composite current collector. As an example, the positive electrode current collector may be an aluminum foil. In the present application, there is no particular restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8μm to 12μm. In the present application, the positive electrode material layer may be disposed on one or two surfaces along the thickness direction of the positive electrode current collector. It should be noted that the "surface" here may be the entire area of ​​the positive electrode current collector or a partial area of ​​the positive electrode current collector. The present application is not particularly limited as long as the purpose of the present application can be achieved.

[0078] In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganate, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, or lithium nickel manganate, and the above positive electrode active material may be doped and / or coated. In some embodiments, the coating element for the coating layer may include K, Na, Ca, Mg, B, Al, Co, Si, V, Ga, Sn, Zr, or a mixture thereof.

[0079] In some embodiments, the positive electrode binder is used to improve the bonding performance between the positive electrode active material particles and the positive electrode active material particles and the current collector. In some embodiments, the positive electrode binder includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon at least one. In some embodiments, the conductive agent includes conductive graphite, superconducting carbon, acetylene black, conductive carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers at least one. Optionally, the positive electrode may also include a conductive layer, which is located between the positive current collector and the positive electrode material layer. The present application does not particularly limit the composition of the conductive layer, and it may be a conductive layer commonly used in the art.

[0080] In some embodiments, the preparation method of the positive electrode sheet is a preparation method of the positive electrode sheet that can be used for an electrochemical device that is well known in the art. In some embodiments, the positive electrode active material and the optional binder and conductive agent are usually dissolved and dispersed in a solvent to prepare a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector, and the positive electrode sheet is obtained through drying, cold pressing and other processes. The solvent is a solvent that can be used as a positive electrode active material layer that is well known in the art, and the solvent is, for example, but not limited to, N-methylpyrrolidone (NMP).

[0081] <Isolation film>

[0082] The separator is a separator known in the art that can be used in electrochemical devices. The electrochemical device of the present application is provided with a separator between the positive electrode and the negative electrode to prevent short circuit. For example, but not limited to, polyolefin microporous membranes. In some embodiments, the separator includes at least one of polyethylene (PE), ethylene-propylene copolymer, polypropylene (PP), ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-methyl methacrylate copolymer.

[0083] In some embodiments, the isolation film is a single-layer isolation film or a multi-layer isolation film.

[0084] In some embodiments, the isolation membrane includes a substrate layer and a surface treatment layer. The material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide or aramid. In some embodiments, the polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. The isolation membrane of the present application may have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01μm to 1μm. In the present application, the thickness of the isolation membrane is not particularly limited, as long as the purpose of the present application can be achieved. For example, the thickness can be 5μm to 500μm.

[0085] In some embodiments, the surface of the isolation membrane may also be provided with a surface treatment layer. The surface treatment layer is provided on at least one surface of the substrate of the isolation membrane, and the surface treatment layer includes at least one of an inorganic layer or a polymer layer. In some embodiments, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (A12O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the electrode. In some embodiments, the polymer material in the polymer layer is selected from at least one of polyacrylonitrile, polyacrylic acid salt, polyamide, polyvinylidene fluoride, and polyvinyl pyrrolidone.

[0086] The method for preparing the isolation membrane in the present application is a method for preparing an isolation membrane that is well known in the art and can be used in electrochemical devices.

[0087] <Housing>

[0088] The housing is used to encapsulate the electrode assembly. In some embodiments, the housing can be a hard shell housing or a flexible shell. The material of the hard shell is, for example, metal. The flexible shell is, for example, a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0089] In some embodiments, the positive electrode sheet, the isolation membrane and the negative electrode sheet can be made into an electrode assembly through a winding process or a lamination process. The electrode assembly is placed in a shell, and an electrolyte is injected. After vacuum packaging, standing, formation, shaping, capacity division and other processes, an electrochemical device can be obtained.

[0090] In other embodiments, the electrochemical device is used in conjunction with a circuit protection board.

[0091] [Electronic devices]

[0092] The present application also provides an electronic device including the above-mentioned electrochemical device. The electronic device of the present application is any electronic device, such as but not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. It is noted that the electrochemical device of the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. Air vehicles include air vehicles within the atmosphere and air vehicles outside the atmosphere.

[0093] The present application is further described below by taking the electrochemical device as a lithium ion battery as an example and combining specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0094] (1) Preparation of electrolyte

[0095] Preparation of electrolytes in Examples 1-1 to 1-23 and Comparative Examples 1-1 to 1-2:

[0096] In an argon atmosphere glove box, a certain mass of EC and DEC are mixed evenly to form a basic solvent, and a lithium salt is dissolved in the basic solvent, wherein the lithium salt is lithium hexafluorophosphate, to obtain an electrolyte, wherein the mass percentage of lithium hexafluorophosphate is 12.5%, and the mass percentage of EC is 25%. A compound of formula I is added to the electrolyte, and the type and content of the compound of formula I are shown in Table 1.

[0097] Preparation of electrolyte in Examples 2-1 to 2-23:

[0098] In an argon atmosphere glove box, a certain mass of EC, PC and DEC are uniformly mixed to form a basic solvent, and a lithium salt is dissolved in the basic solvent, wherein the lithium salt is lithium hexafluorophosphate, to obtain an electrolyte, wherein the mass percentage of lithium hexafluorophosphate is 12.5%. A compound of formula I, a sulfur-oxygen double bond compound or a lithium salt additive is added to the electrolyte, and the content of EC, the content of PC, the type and content of the sulfur-oxygen double bond compound or the content of the lithium salt additive are as shown in Table 2, wherein the type of the compound of formula I is formula I-5, and the mass percentage is 0.05%.

[0099] (2) Preparation of positive electrode

[0100] The positive electrode active material LiMn2O4, the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit and welded to the pole ear to obtain a positive electrode sheet.

[0101] (3) Preparation of isolation membrane

[0102] A polyethylene (PE) porous film is used as the isolation membrane.

[0103] (4) Preparation of negative electrode

[0104] Artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit and weld the pole ears to obtain a negative electrode sheet.

[0105] (5) Preparation of lithium-ion batteries

[0106] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is between the positive electrode and the negative electrode to play an isolating role, and then they are wound to obtain a battery cell; the battery cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried battery cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, the preparation of the lithium-ion battery is completed.

[0107] Next, the performance of lithium-ion batteries is tested:

[0108] (1) Normal temperature cycle performance test

[0109] Place the lithium-ion batteries of the embodiment and comparative example in a 25°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to a voltage of 4.2V, then charge it at a constant voltage of 4.2V to a current of 0.05C, and then discharge it at a constant current of 1C to a voltage of 2.8V. Test the capacity of the lithium-ion battery and record it as C0. This is a cyclic charge and discharge process. Perform a cyclic charge and discharge process on the lithium-ion battery according to the above method for 800 cycles, test the capacity of the lithium-ion battery, and record the capacity as C1. Calculate the cycle capacity retention rate of the lithium-ion battery at 25°C according to the following formula:

[0110] Cycle capacity retention rate (%) = (C1-C0) / C0×100%

[0111] This data is used as an indicator to evaluate the room temperature cycle performance of lithium-ion batteries.

[0112] (2) High temperature cycle performance test

[0113] Place the lithium-ion batteries of the embodiment and comparative example in a 45°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to a voltage of 4.2V, then charge it at a constant voltage of 4.2V to a current of 0.05C, and then discharge it at a constant current of 1C to a voltage of 2.8V. Test the capacity of the lithium-ion battery and record it as C2. This is a cyclic charge and discharge process. Perform a cyclic charge and discharge process on the lithium-ion battery according to the above method for 400 cycles, test the capacity of the lithium-ion battery, and record the capacity as C3. Calculate the cycle capacity retention rate of the lithium-ion battery at 45°C according to the following formula:

[0114] Cycle capacity retention rate (%) = (C3-C2) / C2×100%,

[0115] This data is used as an indicator to evaluate the high temperature cycle performance of lithium-ion batteries.

[0116] (3) High temperature storage thickness growth rate test

[0117] The lithium ion batteries of the embodiment and the comparative example were placed in a constant temperature box at 25°C for 5 minutes, charged to 4.2V at a constant current rate of 1C, and then charged to a current of 0.05C at a constant voltage, and then placed for 5 minutes, and then discharged to 2.8V at a constant current rate of 1C. The thickness of the lithium ion battery at this time was measured and recorded, and recorded as the thickness before high-temperature storage d0. The lithium ion battery was then placed in a constant temperature box at 60°C for 90 days. After that, the lithium ion battery was taken out and its thickness was measured, and recorded as the thickness after high-temperature storage d1. The thickness growth rate of the lithium ion battery was calculated according to the following formula:

[0118] Thickness growth rate = (d1-d0) / d0×100%,

[0119] The lower the thickness growth rate, the better the high-temperature storage performance of the lithium-ion battery.

[0120] (4) DC resistance test (DCR test)

[0121] The lithium-ion batteries of the embodiment and the comparative example were placed in a constant temperature box at 25°C for 5 minutes, charged to 4.2V at a constant current rate of 1C, and then charged to a current of 0.05C at a constant voltage, left to stand for 30 minutes, discharged at a current of 0.1C for 10 seconds (record the corresponding voltage value U1), and discharged at a current of 1C for 360 seconds (record the corresponding voltage value U2), and the DC resistance value (DCR) was calculated according to the following formula:

[0122] R = (U1-U2) / (1C-0.1C).

[0123] (5) Specific surface area (BET) test of negative electrode active materials

[0124] The lithium-ion batteries of the embodiment and the comparative example were disassembled to obtain negative electrode sheets, and the obtained negative electrode sheets were immersed in dispersant ethanol and ultrasonicated for 30 minutes. Thereafter, the obtained negative electrode active materials were placed in a vacuum drying oven for drying. After drying, the specific surface area of ​​the negative electrode active materials was measured using a specific surface area tester (U.S. Quantachrome NOVA2000e).

[0125] (6) Compaction density test of negative electrode

[0126] The lithium-ion batteries of the embodiment and the comparative example were disassembled to obtain negative electrode sheets, and the negative electrode sheets containing the negative electrode active material layer were cut to obtain discs with a diameter of d. The discs were weighed, and the mass was recorded as m1. The calculated disc area was recorded as s1. The disc thickness was measured with a micrometer as h1. The negative electrode current collector was cut to obtain discs with the same diameter of d. The current collector discs were weighed, and the mass was recorded as m2. The measured thickness of the current collector discs was recorded as h2. The compaction density of the negative electrode sheet was calculated according to the following formula:

[0127] Compacted density of negative electrode: e = (m1-m2) / [(h1-h2)×s1]

[0128] In the examples and comparative examples, the types and contents of the additives used are shown in Tables 1 and 2, wherein the content of each additive is the mass percentage calculated based on the total mass of the electrolyte. The specific test results are as follows:

[0129] Table 1 Parameters of Examples 1-1 to 1-23 and Comparative Examples 1-1 to 1-2

[0130]

[0131] Compared with Comparative Example 1-1, Examples 1-1 to 1-11 in Table 1 show that adding the compound of Formula I to the electrolyte can significantly improve the cycle performance and high-temperature storage performance of the lithium-ion battery. This is because the compound of Formula I can form a stable SEI film on the surface of the negative electrode, inhibit the side reaction between the negative electrode and the electrolyte during the cycle and storage process, and reduce the consumption in the electrolyte; in addition, the nitrogen-containing cation part in the compound of Formula I can not only promote the dissociation of the lithium salt, but also complex with Lewis bases such as ethylene carbonate (EC), thereby improving the oxidative stability of the electrolyte and further improving the cycle performance and high-temperature storage performance of the lithium-ion battery.

[0132] The specific surface area of ​​the negative electrode active material will also affect the cycle and high temperature storage performance of the lithium-ion battery. When the specific surface area of ​​the negative electrode active material is too large, it is easy to cause the side reactions on the surface of the negative electrode active material to increase and cause gas production; when the specific surface area of ​​the negative electrode material is too small, the lithium ion transmission speed is slow, affecting the cycle performance of the battery. When the specific surface area of ​​the negative electrode active material is 0.1m 2 / g-5m 2 / g, the cycle performance and high-temperature storage performance of the electrochemical device can be improved; when the specific surface area a of the negative electrode active material and the mass percentage content b% of the compound of formula I satisfy the relationship: 0.1≤a / b≤500, the cycle performance and high-temperature storage performance of the electrochemical device can be significantly improved.

[0133] Table 2 Parameters of Examples 1-21, 2-1 to 2-23

[0134]

[0135]

[0136] Comparison between Example 1-21 and Example 2-1 to 2-23 in Table 2 shows that when the electrolyte includes ethylene carbonate and propylene carbonate, and the sum of the content of ethylene carbonate and the content of propylene carbonate is between 10% and 40%, the cycle performance and high temperature storage performance of the lithium ion battery can be further improved; adding a sulfur-oxygen double bond compound within the scope of this application to the electrolyte can further improve the high temperature storage performance of the lithium ion battery, because the sulfur-oxygen double bond compound can form a dense and low impedance protective film on the surface of the positive and negative electrodes, reduce the side reaction between the positive and negative electrodes and the electrolyte, and reduce the thickness growth rate of the lithium ion battery during high temperature storage; adding a lithium salt additive within the scope of this application to the electrolyte can further improve the cycle performance of the battery, and the lithium salt additive can form a film at the positive and negative electrodes, improve the stability of the positive and negative electrode interfaces, and improve the cycle performance of the battery. The combined use of the above additives can simultaneously increase the stability of the positive and negative electrodes of the lithium ion battery, and effectively improve the high temperature storage performance and cycle performance of the lithium ion battery.

[0137] The above disclosed features are not intended to limit the scope of implementation of the present disclosure. Therefore, all equivalent changes made to the contents described in the claims of the present disclosure should be included in the scope of the claims of the present disclosure.

Claims

1. An electrochemical device comprising a negative electrode sheet and an electrolyte, The electrolyte comprises a compound shown in formula I, in, R1 is selected from any one of substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C1 to C6 alkoxy, substituted or unsubstituted C2 to C6 alkenyl, wherein when substituted, the substituent is selected from cyano and halogen atom; R2, R3, R4, R5 and R6 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C2 to C 10 Alkenyl, substituted or unsubstituted C2 to C 10 Alkynyl, substituted or unsubstituted C2 to C 10 Any one of the heterocyclic groups, wherein, when substituted, the substituent is a halogen atom; The substituted or unsubstituted C2 to C 10 The heterocyclic group includes substituted or unsubstituted C6 to C 10 Aromatic heterocyclic group, substituted or unsubstituted C2 to C 10 Alicyclic group, wherein the heteroatom is selected from N or O; The negative electrode sheet includes a negative electrode active material, and the specific surface area of ​​the negative electrode active material is am 2 / g, the value range of a is 0.1-5; Wherein, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%; The a and b satisfy the relationship: 0.1≤a / b≤500; The electrolyte further comprises a compound containing a sulfur-oxygen double bond; the compound containing a sulfur-oxygen double bond comprises 1,3-propane sultone and methylene disulfonate; based on the mass of the electrolyte, the mass percentage of the compound containing a sulfur-oxygen double bond is f%, and the value range of f is 1-3; The electrolyte also includes a lithium salt additive; the lithium salt additive includes lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage content of the lithium salt additive is g%, and the value range of g is 0.01-3.

2. The electrochemical device according to claim 1, wherein: The compound of formula I includes any one of the following structural formulas:

3. The electrochemical device according to claim 1, wherein Based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%, and the value range of b is 0.005-3.

4. The electrochemical device according to claim 1, wherein The electrolyte also includes ethylene carbonate and propylene carbonate; Based on the mass of the electrolyte, the content of ethylene carbonate is c%, the content of propylene carbonate is d%, and c and d satisfy the relationship: 10≤c+d≤40.

5. The electrochemical device according to claim 1, wherein The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector; The compaction density of the negative electrode active material layer is eg / cm 3 , the value range of e is 1-2.

6. The electrochemical device according to claim 1, wherein The compound containing sulfur-oxygen double bonds further comprises at least one of 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propane disulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate.

7. The electrochemical device according to claim 1, wherein: The lithium salt additive further includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium difluorophosphate or lithium trifluoromethanesulfonate.

8. The electrochemical device according to claim 1, which satisfies one of the following conditions: (1) The specific surface area of ​​the negative electrode active material is am 2 / g, the value range of a is 0.5-3.5; (2) The specific surface area of ​​the negative electrode active material is am 2 / g, based on the mass of the electrolyte, the mass percentage of the compound of formula I is b%, and a and b satisfy the relationship: 0.8≤a / b≤300; (3) Based on the mass of the electrolyte, the mass percentage of the compound of formula I is 0.005% to 1%.

9. The electrochemical device according to claim 1, wherein: Any two groups among R2, R3, R4, R5 and R6 are bonded to form a ring structure.

10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrochemical device and electronic device

    CN114188504A

  • Nonaqueous electrolytic solution secondary battery and nonaqueous electrolytic solution

    WO2021187625A1